Faunistic inventory, identification keys and zoogeographical analysis of the Thysanoptera-Terebrantia of Saudi Arabia, including two new species - Rasool, Iftekhar; Alattal, Yehya Zaki; Aldhafer, Hathal M. (Zootaxa, 2023)
This faunistic study of the Thysanoptera suborder Terebrantia of Saudi Arabia has revealed 79 species in 39 genera and four families. Two families Melanthripidae Bagnall and Stenurothripidae Bagnall, also 25 genera and 51 species, are newly recorded for Saudi Arabia, and Mycterothrips arabicus sp. n. and Scirtothrips erectus sp. n., are described. Males of Thrips lomatus zur Strassan and Odontothrips elbaensis Priesner are described for the first time. Keys to the families, genera and species of Terebrantia of Saudi Arabia are presented, together with a species check list. Zoogeographical analysis indicates that general affinity of the thrips fauna of Saudi Arabia is dominated by Afrotropical (22.6%) and Saharo-Arabian (17.9%) species, followed by Cosmopolitan (16.7%), endemic (11.9%), Palearctic (10.7%), Oriental (9.5%), Mediterranean (7.1%), and traces of Nearctic (2.4%) and Holarctic (1.2%) species.